Konflikt i usaglašavanje energetske politike i politike zaštite okoliša u Bosni i Hercegovini / Conflict and Reconciliation of Energy Policy and Environmental Policy in Bosnia and Herzegovina - Kuka, Ermin (Pregled: časopis za društvena pitanja / Periodical for social issues, 2018)
There is a number of essential questions and problems conected to a conflict and reconciliation of energy policy and environmental policy that need to be elaborated with the goal of securing the starting basics for consonencing and integrenaising these mutually oposing public themes. Therefore a strong accent is set on proceses of advocacy, implementing, colaborate consonencing and integration of these two strategicly public policies of every country with a special review on state and posabilities in Bosnia and Herzegovina. That is also a key problem and a subject of this research. Having in sight a problem and subject stated above we start from general hypothesis how aformating strategic partnerships and building cooperative relationships, energy policy can asure coresponding resource basis that is usually limited, thus giving the support to a faster growth and development in bh economy, with that also it must preserve envioronment. That means simultaneously consiliating needed economic progres and social cohesion with full envioronmental protection. Results provided by empirical research can be of importance for finding an acceptable solution to an evident conflict to these two relative and public policies and in function securing asumptions to a sustainable progres of bh economy.